(untitled) (Journal of Geography and Environmental Management, 2023)
Tourism is an actively developing branch of the economy. Despite the fact that Kazakhstan’s tourist destinations are not yet widely represented on the world tourism market, having unique natural resources and objects of cultural and historical heritage, the country has a huge potential for a worthy place in world tourism. All the necessary cultural, historical, geographical and climatic conditions are sufficient for the development of tourism in the country. There are three cultural heritage sites and two natural heritage sites listed as UNESCO World Heritage Sites in Kazakhstan. However, the attractiveness of the tourism industry is characterized not only by beautiful natural landscapes and historical sites, but also by developed infrastructure and services, access to transport and security. The regions of interest to domestic and foreign tourists in the republic are national parks and specially protected natural areas. The most popular destinations among Kazakhstanis are the cities of Almaty and Astana, as well as the East Kazakhstan region, and the most popular among foreign tourists is the Almaty cluster. There are opportunities in the regions of Kazakhstan to increase the share of this industry in the country’s economy through the development of tourism. To do this, it is necessary to solve the current problems of the development of the industry.